DESIGN AND DEVELOPMENT OF THE LIDI DITENUN MODULE FEATURE IN MOTIF MERGING AND COLORING, AND EVALUATION METHOD - Arlinta Christy Barus; Humasak Tommy Argo Simanjuntak; Itha Clarina Br Tarigan; Cindy Feronica Simangunsong; Riskia Naomi Sitorus; Samuel Indra Gunawan Situmeang; Herimanto (MATTER: International Journal of Science and Technology, 2025)
Preserving woven fabric cultural heritage requires digital innovation to appeal to younger generations. This research presents the Lidi Module on DiTenun website, enabling digital combination and coloring of woven motifs using traditional lidi techniques. Developed with Waterfall method and User Centered Design, the module underwent iterative usability evaluation through heuristic and participatory evaluation by experts and users. The System Usability Scale scored 82.5, indicating very good usability. Results show the Lidi Module effectively supports digital motif creation, combination, and coloring with intuitive workflow, demonstrating significant potential for preserving and innovating traditional weaving culture through digital platforms.